2016
DOI: 10.3389/fnagi.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval Deficiency in Brain Activity of Working Memory in Amnesic Mild Cognitive Impairment Patients: A Brain Event-Related Potentials Study

Abstract: In the early stage of Alzheimer disease (AD) or mild cognitive impairment (MCI), working memory (WM) deficiency is prominent and could be attributed to failure in encoding, maintenance or retrieval of information. However, evidence for a retention or retrieval deficit remains equivocal. It is also unclear what cognitive mechanism in WM is impaired in MCI or early AD. We enrolled 46 subjects from our Memory Clinics and community, with 24 amnesic MCI patients and 22 normal subjects. After neurological and cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Importantly, we found the reduction speci cally in the maintenance and retrieval phase of memory. As in our previous work, retrieval de ciencies could be the cause of poor performance (5). An intervention study provided additional evidence for the importance of the retrieval phase in recognition (34).…”
Section: Network 1 Connectivity Is Predominantly Impaired In Adsupporting
confidence: 65%
See 1 more Smart Citation
“…Importantly, we found the reduction speci cally in the maintenance and retrieval phase of memory. As in our previous work, retrieval de ciencies could be the cause of poor performance (5). An intervention study provided additional evidence for the importance of the retrieval phase in recognition (34).…”
Section: Network 1 Connectivity Is Predominantly Impaired In Adsupporting
confidence: 65%
“…It is controversial whether the observed amnesia is due to disrupted encoding or consolidation of episodic information, or an impairment in the retrieval of stored memory information. Several studies have suggested that the ineffective encoding of new information in the brain triggers episodic memory de cits (1,2), while more evidence supported retrieval de cit in early AD (3)(4)(5). Transgenic AD mouse models also suggested that direct activation of hippocampal memory engram cells resulted in memory retrieval, revealing a retrieval, rather than a storage impairment in early AD (6).…”
Section: Introductionmentioning
confidence: 99%
“…P200 latency was longer in the high-load condition than in the low-load condition, indicating the need for more processing time in the more difficult conditions. Previous studies have found no effect of task difficulty on the P200 (Li et al, 2016;Pinal et al, 2014). These conflicting findings may be due to differences in stimulus presentation: Li et al (2016) presented letters for 2000 ms whereas Pinal and Diaz, 2014 presented domino images for 1000 ms, and both studies presented all stimuli for the same time independent of memory load.…”
Section: Encodingmentioning
confidence: 84%
“…This component is typically measured during conflict monitoring tasks (Veen & Carter, 2002), but is also reflective of stimulus detection and the ability to discriminate incongruities between stimuli (Bennys, Portet, Touchon & Rondouin, 2007;Folstein & Van Petten, 2008;Patel & Azzam, 2005). Similar to the P2, in a DMS task N2b amplitude is not modulated during encoding by task difficulty (Li et al, 2016;Pinal et al, 2014). However, during the retrieval phase of a WM task, N2b amplitude continually increases with task difficulty (Patel & Azzam, 2005;Pinal et al, 2014), indicating that as the task becomes more difficult, more attention and effort is needed to retrieve the memory of the past stimulus and discriminate the current stimulus from the previous one.…”
Section: Introductionmentioning
confidence: 99%
“…For the source localization, the low-resolution electromagnetic tomography approach was applied, which has been previously successfully used for the analysis of ERPs in MCI patients [33,34]. However, to our knowledge, this is the first study examining the sources of induced time-varying oscillations in MCI.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%